Pengaruh Prinsip Good Corporate Governance (GCG) Terhadap Hutang Piutang Berdasarkan Surat Al-Baqarah Ayat 280-283 - Rofidah, Lailia; Yulandari, Miftahul; Djasuli, Mohamad (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
Abstract This research is intended to find out how the influence of the principles of Good Corporate Governance (GCG) on receivables based on Al-Baqarah verses 280-283. This study uses a qualitative descriptive approach as well as primary data & secondary data. Primary data quoted from Al-Qur'an Al-Baqarah verses 280-283, then secondary data was taken from journals, hadiths, books, internet, and other literature. The results of this study are that the principles of GCG, Accounts Payable, and Surah Al-Baqarah verses 280-283 are interconnected and interrelated with one another.The abstract should be in one paragraph.The font is